2011
DOI: 10.1016/j.eatbeh.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Objectified body consciousness in relation to recovery from an eating disorder

Abstract: In Western society, the feminine body has been positioned as an object to be looked at and sexually gazed upon; thus, females often learn to view themselves as objects to be observed (i.e., objectified body consciousness (OBC)). This study examined the relation between OBC and eating disorder recovery by comparing its components across non-eating disorder controls, fully recovered, partially recovered, and active eating disorder cases. Results revealed that non-eating disorder controls and fully recovered indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 56 publications
5
54
1
Order By: Relevance
“…These findings extend prior studies conducted with men which identified that the potential pathogenic effect of negative body image-related experiences depends on the extent to which these experiences relate to the sense of one's value within the social group (Adams et al, 2005;Calogero, 2009;Dakanalis et al, 2012;Dakanalis & Riva, 2013;Fitzsimmons-Craft, 2011;Grogan & Richards, 2002;McCabe & Ricciardelli, 2003;McCreary & Sasse, 2002). These findings also add to recent evidence that highlighted the roles that body image dissatisfaction and shame play in binge eating symptoms in men (Dakanalis et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These findings extend prior studies conducted with men which identified that the potential pathogenic effect of negative body image-related experiences depends on the extent to which these experiences relate to the sense of one's value within the social group (Adams et al, 2005;Calogero, 2009;Dakanalis et al, 2012;Dakanalis & Riva, 2013;Fitzsimmons-Craft, 2011;Grogan & Richards, 2002;McCabe & Ricciardelli, 2003;McCreary & Sasse, 2002). These findings also add to recent evidence that highlighted the roles that body image dissatisfaction and shame play in binge eating symptoms in men (Dakanalis et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, whereas conceptions of traditional masculinity convey the notion that men's worth is related to their abilities to be powerful, socially dominant, and physically effective (Kilmartin, 2007), women constantly face messages that their worth depends on how their physical appearance is perceived by others (Fredrickson & Roberts, 1997), which negatively affects their selfevaluation, body image, and eating behaviour (Fitzsimmons-Craft et al, 2011;Dakanalis et al, 2015;Dakanalis, Clerici, et al, 2014; being seen by others as flawed, unattractive or inferior, as well as to the internal shaming process that includes severe self-criticism (Goss & Allan, 2009;Goss & Gilbert, 2002;. Binge eating symptoms may be adopted in this context as a means to cope with such negative evaluations and emotions Duarte et al, 2015a).…”
Section: The Effect Of Gendermentioning
confidence: 99%
See 2 more Smart Citations
“…They ''internalize cultural body standards so that the standards appear to originate from the self and believe that achieving these standards is possible even in the face of considerable evidence to the contrary'' (p. 183). OBC has been used to explain gender differences in body esteem (McKinley, 1998), to understand psychological well-being between mothers and daughters (McKinley, 1999), and to document behavioral differences in eating disorder recovery (Fitzsimmons-Craft, Bardone-Cone, & Kelly, 2011). OBC has been used to explain gender differences in body esteem (McKinley, 1998), to understand psychological well-being between mothers and daughters (McKinley, 1999), and to document behavioral differences in eating disorder recovery (Fitzsimmons-Craft, Bardone-Cone, & Kelly, 2011).…”
Section: Literature Review and Hypotheses Development Obcmentioning
confidence: 99%